Type a math problem

This site uses cookies for analytics, personalized content and ads. By continuing to browse this site, you agree to this use. Learn more

Type a math problem

Solve for a

a=\frac{3b}{b-2},b\neq 2

$a=b−23b ,b =2$

Steps for Solving Linear Equation

a \cdot (b-2) = 3b

$a⋅(b−2)=3b$

Use the distributive property to multiply a by b-2.

Use the distributive property to multiply $a$ by $b−2$.

ab-2a=3b

$ab−2a=3b$

Combine all terms containing a.

Combine all terms containing $a$.

\left(b-2\right)a=3b

$(b−2)a=3b$

Divide both sides by b-2.

Divide both sides by $b−2$.

\frac{\left(b-2\right)a}{b-2}=\frac{3b}{b-2}

$b−2(b−2)a =b−23b $

Dividing by b-2 undoes the multiplication by b-2.

Dividing by $b−2$ undoes the multiplication by $b−2$.

a=\frac{3b}{b-2}

$a=b−23b $

Solve for b

b=\frac{2a}{a-3},a\neq 3

$b=a−32a ,a =3$

Steps for Solving Linear Equation

a \cdot (b-2) = 3b

$a⋅(b−2)=3b$

Use the distributive property to multiply a by b-2.

Use the distributive property to multiply $a$ by $b−2$.

ab-2a=3b

$ab−2a=3b$

Subtract 3b from both sides.

Subtract $3b$ from both sides.

ab-2a-3b=0

$ab−2a−3b=0$

Add 2a to both sides. Anything plus zero gives itself.

Add $2a$ to both sides. Anything plus zero gives itself.

ab-3b=2a

$ab−3b=2a$

Combine all terms containing b.

Combine all terms containing $b$.

\left(a-3\right)b=2a

$(a−3)b=2a$

Divide both sides by a-3.

Divide both sides by $a−3$.

\frac{\left(a-3\right)b}{a-3}=\frac{2a}{a-3}

$a−3(a−3)b =a−32a $

Dividing by a-3 undoes the multiplication by a-3.

Dividing by $a−3$ undoes the multiplication by $a−3$.

b=\frac{2a}{a-3}

$b=a−32a $

Share

Copy

Copied to clipboard

ab-2a=3b

Use the distributive property to multiply a by b-2.

\left(b-2\right)a=3b

Combine all terms containing a.

\frac{\left(b-2\right)a}{b-2}=\frac{3b}{b-2}

Divide both sides by b-2.

a=\frac{3b}{b-2}

Dividing by b-2 undoes the multiplication by b-2.

ab-2a=3b

Use the distributive property to multiply a by b-2.

ab-2a-3b=0

Subtract 3b from both sides.

ab-3b=2a

Add 2a to both sides. Anything plus zero gives itself.

\left(a-3\right)b=2a

Combine all terms containing b.

\frac{\left(a-3\right)b}{a-3}=\frac{2a}{a-3}

Divide both sides by a-3.

b=\frac{2a}{a-3}

Dividing by a-3 undoes the multiplication by a-3.

Back to top